Wasp Neodryinus typhlocybae Ashmead – successful predator and parasitoid for reducing the population of flatid planthopper (Metcalfa pruinosa Say) also in Slovenia - Ivan ŽEŽLINA; Lea MILEVOJ; Vincenzo GIROLAMI (Acta Agriculturae Slovenica)
Metcalfa pruinosa Say has been present in Slovenia for more than a decade and has been gradually, but constantly spreading also because of the reason that for the time being we do not have an efficient autochthonous natural enemy that could limit such great population in number and its spreading to the central parts of the country. The wasp Neodryinus typhlocybae Ashmead is in the North and South America and after its introduction to Italy also in Europe the main antagonistic organism for the limitation of spreading of flatid planthopper. With the introduction of the wasp to Slovenia we have wanted to limit the spreading of flatid planthopper, to reduce the population and so to establish a partly biological balance between these two species. In the research we were observing time adjustment between the hatching of the wasp and the appearance of different evolutionary stages regarding flatid planthopper and the appearance of the second incomplete generation of the wasp which is important for predatory and parasitoid effect. We were also doing research into successful settlement of the wasp into a natural habitat on two locations in the Primorska region.